Improving the quality of design documents: Towards sustainable Indonesian government project performance - Suwandi; Hardjomuljadi, Sarwono; Gondokusumo, Onnyxiforus; Sari, Endah Murtiana; Najid (International Journal of Innovative Research and Scientific Studies, 2025)
The quality of design documents in government projects is very important due to state interests and the substantial funds required. The delays often experienced are due to the poor quality of design documents, which leads to a high frequency of change orders. Therefore, this study aimed to identify significant factors influencing the quality of design documents in order to improve government project implementation. A Schematic Literature Review (SLR) and Focus Group Discussion (FGD) were conducted through the Delphi method for two rounds to produce a matrix of factors to be considered in improving the quality of design documents in government projects. The results are expected to be useful for enhancing the quality of design documents to ensure sustainable government projects with high performance in terms of cost, quality, time, safety, and environment. Moreover, government project contractors can use this study to improve the quality of design documents and project performance.